Could Statin Therapy Be Useful in Patients With Coronavirus Disease 2019 (COVID-19)? - Torres-Peña, Jose D.; Katsiki, Niki; Perez-Martinez, Pablo (Frontiers in Cardiovascular Medicine, 2021)
Acute respiratory distress syndrome (ARDS), resulting from an exaggerated inflammatory response, is the main cause of death from the coronavirus disease 2019 (COVID-19). Apart from respiratory infection, COVID-19 patients can develop cardiovascular disorders such as myocardial injury and myocarditis, pericarditis, cardiac arrest and arrhythmias, cardiomyopathy, heart failure, coagulation abnormalities and thrombosis. Statins can beneficially affect inflammation, oxidative stress, coagulation, thrombosis, angiotensin converting enzyme receptor, lipid rafts and endothelial function. In this narrative review, we provide a critical overview of the current evidence and future perspectives on the use of statins to modulate the severity, duration and complications of COVID-19 through their pleiotropic properties.